DIFFERENT SURGICAL MANIFESTATIONS OF MENINGIOMAS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Meningiomas are among the most common primary intracranial tumors arising from the meningothelial cells of the arachnoid layer. Though typically benign, their surgical manifestations vary significantly depending on their size, location, vascular supply, and relationship with adjacent neurovascular structures. Surgical management remains the mainstay of treatment, and understanding the diverse presentations of meningiomas is critical for neurosurgeons. Supratentorial meningiomas, such as those located at the convexity or parasagittal region, often present with seizures or focal neurological deficits, and can be accessed relatively easily via craniotomy. In contrast, skull base meningiomas—including sphenoidal wing, clinoid, and petroclival types—pose greater surgical challenges due to their proximity to cranial nerves and vital vasculature [1]. Spinal meningiomas, though less common, require a different surgical approach and frequently result in symptoms of cord compression. Moreover, certain meningiomas exhibit invasive behavior or recur after resection, necessitating complex surgical strategies, including staged operations or combination with adjuvant therapies. Technological advancements, such as neuronavigation, intraoperative imaging, and microsurgical techniques, have greatly improved surgical outcomes. A tailored approach considering tumor pathology, anatomical complexity, and patient-specific factors remains essential in achieving optimal resection and minimizing morbidity.